Exploring Factors Influencing User Avoidance Behavior Toward QR-Based Payment Scams - Angelique Aurielle Alpaullivarez; Ahmad Nurul Fajar (Universitas Airlangga, 2026)
Background: QR Code Phishing (Quishing) is one of the phishing threats using QR codes that are currently rampant in the use of QR-based payment systems as a digital payment tool. Research related to avoiding Quishing threats in QR-based payment systems is still limited, where previous research has discussed more about phishing threats. Objective: This research aims to determine the factors that influence QR-based payment users avoidance behavior towards Quishing threat by using the Technology Threat Avoidance Theory (TTAT) model. Methods: This research collected data via Google Form questionnaire from 469 QR-based payment users in the Jakarta Municipality area, Indonesia through purposive sampling. The data was then analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) method. Results: The results show that 10 of the 11 hypotheses are accepted. Perceived Severity (SEV), Perceived Susceptibility (SUS), and Distrust Propensity (DIST) significantly influenced Perceived Threat (THR). Meanwhile, Risk Propensity (RSK) has no influence on Perceived Threat (THR). Perceived Threat (THR), Impulsivity (IMP), Safeguard Effectiveness (EFF), Safeguard Cost (CST), Self Efficacy (SLF) significantly influenced Avoidance Motivation (MOT). Avoidance Motivation (MOT) has a significant influence on Avoidance Behavior (BEH). System Trust (ST) has a moderate effect on the relationship between Avoidance Motivation (MOT) and Avoidance Behavior (BEH). Overall, The TTAT model contributed 55.1% to explaining the influence of QR-based payment users avoidance behavior. Conclusion: This study shows that the avoidance actions of QR-based payment users in Indonesia are influenced by Avoidance Motivation. Avoidance motivation is influenced by Perceived Threat, Self Efficacy, Safeguard Effectiveness, Safeguard Cost, Impulsivity. Also, System Trust also significantly moderates its influence on avoidance behavior. This is a guide for QR service providers to improve security in QR-based payment transactions and preventive education steps for QR-based payment users to avoid the threat of Quishing. Keywords: Quishing, Avoidance Behavior, Technology Threat Avoidance Theory, QR-based payment